3D Turntables: Humanizing Architectural Technology Through Hip-Hop. Issue 2 (3rd July 2019) - Cooke, Sekou
Abstract : This paper explores the potential impacts of hip-hop culture on architectural technology through arguments on humanizing technology, embracing a post-Western mindset, and reflecting cultural values within creative products. It further documents the results of a design research study that sought to explore the architectural applicability of digital fabrication techniques derived from hip-hop DJ performance. By understanding the DJ's ability to humanize technology through manual manipulation of analog and digital phonographic equipment, new design methodologies emerged—including the architectural application of "scratch, " "spin, " and "cross-fade" DJ techniques—that deploy a set of disruptions to the 3-D printing process with the potential to transform derelict buildings into community assets.